Harry Mulisch : Zielespiegel : Bij wijze van catalogus. - Borges, Jorge Luis, 1899-1986.; De Quincey, Thomas; Enzensberger, Hans Magnus; Fuchs, Rudi H.; Gautier, Théophile; Hugo, Victor; Mulisch, Harry; Nodier, Charles; Vestdijk, Simon (Amsterdam : De bezige bij, 1997)
Alma-Tadema, Lawrence ; Bell, Larry ; Chagall, Marc ; Citroen, Paul ; Van Haarlem, Cornelis Cornelisz ; Darboven, Hanne ; De Chirico, Giorgio ; Dürer, Albrecht ; van Gogh, Vincent ; Goltzius, Hendrik ; Kandinsky, Wassily ; Kiefer, Anselm ; Klee, Paul ; Kounellis, Jannis ; Lang, Fritz ; Lüpertz, Markus ; Malevich, Kasimir ; Mariani, Carlo Maria ; Masereel, Frans ; Mondriaan, Piet ; Nauman, Bruce ; Paolini, Giulio ; Picasso, Pablo ; Piranesi, Giovanni Battista ; Rainer, Arnulf ; Rembrandt ; Rückriem, Ulrich ; Schwitters, Kurt ; Vordemberge-Gildewart, Friedrich
biografie
Zielespiegel, Stedelijk Museum Amsterdam, 07.12.1997 - 15.02.1998
Nederlands
boek